Comparative Transcriptome and Endophytic Bacterial Community Analysis of Morchella conica SH - Lü, Bei B.; Wu, Guo G.; Sun, Yu; Zhang, Liang S.; Wu, Xiao; Jiang, Wei; Li, Peng; Huang, Yan N.; Wang, Jin B.; Zhao, Yong C.; Liu, Hua; Song, Li L.; et al. (Frontiers in Microbiology, 2021)
The precious rare edible fungus Morchella conica is popular worldwide for its rich nutrition, savory flavor and varieties of bioactive components. Due to its high commercial, nutritional and medicinal value, it has always been a hot spot. However, the molecular mechanism and endophytic bacterial communities in M. conica SH were poorly understood. In this study, we sequenced, assembled and analyzed the genome of M. conica SH. Transcriptome analysis reveals that significantly differences between mycelia and fruiting body. As shown, 1329 and 2796 genes were specifically expressed in mycelium or fruiting body, respectively. The GO enrichment showed that RNA polymerase II transcription activity related genes were enriched in mycelium specific gene cluster, and nucleotide binding related genes were enriched in fruiting body specific gene cluster. Further analysis of differential expressed genes between different development stages, two groups with distinct expression pattern were found. KEGG pathway enrichment display that glycan degradation and ABC transporters were enriched in the group with high expressed level in mycelia, while taurine and hypotaurine metabolism and tyrosine metabolism related genes were significantly enriched in the group with low expressed level in mycelia. Moreover, dynamic shift of bacterial communities in development fruiting body were detected by 16S rRNA sequencing, and co-expression analysis suggested that bacterial communities might play an important role in regulating gene expression. Taken together, our study provided a better understanding in the molecular biology of M. conica SH and direction for future research on artificial cultivation.